PERAN KEMAMPUAN SPASIAL (SPATIAL REASONING) DALAM PEMBELAJARAN GEOMETRI SISWA DI SEKOLAH DASAR - nurhanifa, Syafira Nurhanifa; Siti Faizah; Riska Pristiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Spatial ability is a critical cognitive skill in elementary school students’ geometry learning because it helps them visualize, manipulate, and reason about the relationships between spatial objects. However, geometry education still faces challenges in optimally developing this ability. This study aims to examine the role of spatial ability through a Systematic Literature Review (SLR) of national articles from the past five years accessed via Google Scholar. Literature selection was based on topic relevance, the elementary school level, and a focus on spatial ability and geometry. This study highlights the forms of spatial ability, its role in conceptual understanding, and its implications for more visual and contextual learning, thereby serving as a foundation for the development of geometry learning strategies.